PROBLEMATIQUE DE L’EQUIPEMENT DANS LA SOUS-PREFECTURE DE BONON - épse Yapi, Seri Zohonon Sylvie-Céline (European Scientific Journal, ESJ, 2014)
This work analyses the equipment problems in the sub-prefecture of Bonon. For, thanks to information collected with the competent services (Ministry of Plan, General Council of Bouaflé) and a field survey, we came to highlight the equipment state of the area. The study led us to the conclusion that Bonon benefited from the local State- Population partnership regarding the construction of modern infrastructures. But in the course of years, those equipments became damaged. Additionally, the population pressure makes them overused so that they become unadapted to the needs of the populations. With the States withdrawal, decentralization is perceived as the way out of the crisis to revive the equipment policy. In spite of the investments achieved by the General Council, the sub-prefecture of Bonon is still underequipped. The cash shortage of the new local authorities limits their investment possibilities and thwarts the implementation of local equipment projects.